Where Was COVID-19 First Discovered? Designing a Question-Answering System for Pandemic Situations - Graf, Johannes; Lancho, Gino; Zschech, Patrick; Heinrich, Kai (Proceedings of the 30th European Conference on Information Systems, 2022)
The COVID-19 pandemic is accompanied by a massive “infodemic” that makes it hard to identify concise and credible information for COVID-19-related questions, like incubation time, infection rates, or the effectiveness of vaccines. As a novel solution, our paper is concerned with designing a question-answering system based on modern technologies from natural language processing to overcome information overload and misinformation in pandemic situations. To carry out our research, we followed a design science research approach and applied Ingwersen’s cognitive model of information retrieval interaction to inform our design process from a socio-technical lens. On this basis, we derived prescriptive design knowledge in terms of design requirements and design principles, which we translated into the construction of a prototypical instantiation. Our implementation is based on the comprehensive CORD-19 dataset, and we demonstrate our artifact’s usefulness by evaluating its answer quality based on a sample of COVID-19 questions labeled by biomedical experts.<br
Keywords: COVID-19; Information Retrieval; Question-Answering; Design Science Research; Inklusion